The Meaning and Interpretation of the "Vulture's Feather" in the Shahnameh - hassan heydari; Ali Sabbaghi (Matn/Pizhūhī-i Adabī, 2015)
This study seeks to describe and discuss a hemistich, namely ‘‘yours the earth, mine the vulture’s feather’’, of the story of Rostam and Sohrab in Ferdowsi's Shahnameh. Many commentators and interpreters of the Shahnameh have different opinions on the concept and meaning of this hemistich. This has led the researchers to seek the reason of such differences, clues for the provided meanings, and the underlying concept of this verse. The researchers hypothesize that the low frequency of occurrence of the phrase ‘‘yours the earth, mine the vulture’s feather’’ in Persian texts has resulted in the ambiguity in the interpreting the verse, and in addition, this has also misguided the commentators to report the verse holistically. The researchers have found new evidence for the interpretation of ‘‘the vulture's feather’’ through the tools of analogy and diachronic analysis, and finally have provided a new meaning for the verse. The findings of the research, on the one hand, suggest that the interpretation of ‘‘vulture's feather’’ in this verse connotes tininess, diminution, and nothingness in comparison with the earth and whatever is on it. On the other hand, the interpretation of ‘‘borrowing vulture's feathe’’ is used to connote precipitation and haste.